The use of personal names among Slovakia Hungarians - Bauko, Ján (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
This study deals the use of personal names among Slovakia Hungarians. The bilingual environment of Slovakia Hungarians affects their use of personal names. Bilingual persons can choose names from a larger set of names. Choosing a variant of a personal name from one language or the other can depend on several factors: the communicative domain, the communication partners, the social or linguistic context etc. The dimensions of time, space and society play an important role in the change anddiversity of personal names. A Hungarian dominant use of names characterizes Slovakia Hungarians in the informal domains, and Slovak dominant use in the formal domains. A dual use of names or bi-naming can characterize a dual identity, however, most people employ this as a pre-emptive strategy trying to avoid a possible language or communication problem by using the form conforming with the majority norm in a majority language context and the form conforming with the minority norm in a minority language or informal context. Personal names have an identity marking function, and can indicate the language affiliation and nationality of their bearer.